Dampak Adanya Influencer Investor Serta Perilaku Fear Of Missing Out (FOMO) Terhadap Keputusan Pembelian Saham Di Indonesia - Iasa Nur Firdausi; Lia Nirawati (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
In the digital era like today, investment itself can be interpreted as an activity of placing capital or wealth owned by someone with the reason to gain profits in the future. It is also not uncommon to find some investors who deliberately show the condition of their stock portfolio with the intention of providing guidance to the general public regarding the investment activities they have carried out. In general, an influencer investor provides educational narratives to his followers by providing an overview or even a visualization of their experiences in stock investing activities. Influencer investors often provide an overview of the amount of profits that have been obtained with persuasive narratives so that they can attract followers' interest in doing things similar to what the influencer investors did. It doesn't stop there, the decision to buy shares is often also based on the responses given by followers of other investor influencers. The response of an investor influencer follower often results in a persuasive share purchase decision. This is often also known as the condition of being trapped by an investor in a FOMO phenomenon or Fear of Missing Out.